2020
DOI: 10.1002/cbic.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Based Nanozymes in Disease Diagnosis and Treatment

Abstract: Iron-based nanozymes are currently one of the few clinical inorganic nanoparticles for disease diagnosis and treatment. Overcoming the shortcomings of natural enzymes, such as easy inactivation and low yield, combined with their special nanometer properties and magnetic functions, iron-based nanozymes have broad prospects in biomedicine. This minireview summarizes their preparation, biological activity, catalytic mechanism, and applications in diagnosis and treatment of diseases. Finally, challenges to their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…It is generally believed that iron-based NPs can react with H 2 O 2 to cause Fenton reaction and produce ·OH, thus mediating biotoxicity. 29 Therefore, the assessment of whether PTCN can undergo Fenton reaction was crucial for the correct evaluation of ROS-scavenging activity and the potential biosafety of PTCN. As shown in Figure S10 , the FeSO 4 and H 2 O 2 system has been considered a classic Fenton reaction model, and the produced ·OH could specifically react with salicylic acid to form 2,3-dihydroxybenzoic acid, exhibiting an obvious UV absorption peak at 510 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that iron-based NPs can react with H 2 O 2 to cause Fenton reaction and produce ·OH, thus mediating biotoxicity. 29 Therefore, the assessment of whether PTCN can undergo Fenton reaction was crucial for the correct evaluation of ROS-scavenging activity and the potential biosafety of PTCN. As shown in Figure S10 , the FeSO 4 and H 2 O 2 system has been considered a classic Fenton reaction model, and the produced ·OH could specifically react with salicylic acid to form 2,3-dihydroxybenzoic acid, exhibiting an obvious UV absorption peak at 510 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Metal-based nanoparticles are well known to mimic POD and OXD activity, with promising applications in therapeutics. Metal-based nanozymes are in vogue owing to their easy synthesis and facile surface modification and convenience to hybridize with other elements and tailor their shape-size, high stability, biocompatibility, and electromagnetic functionality ( Li M. et al, 2020 ; Shi et al, 2020 ). For instance, Xi et al have shown that the doping of Cu in hollow carbon spheres (Cu-HCS) accelerated their POD activity ( Xi et al, 2019 ).…”
Section: Composite Nanozymes With Pro-oxidative Potentialmentioning
confidence: 99%
“…With the discovery of the enzymatic properties of iron oxide nanoparticles (Fe3O4 NPs) and iron-based NPs (Au@Fe3O4 [54], Fe3O4 coated Ag [55], Pt48Pd52-Fe3O4 [56], Fe3O4@Pt [57], metal organic framework-based MnFe2O4/C nanozymes, [58], etc. ), new attention has focused on bioapplications of peroxidaselike Fe3O4 nanostructures [38,59]. For instance, cobalt-doped Magnetoferritin (M-HFn) NPs (M-HFn-Cox Fe3-x O4) with different amounts of cobalt were successfully synthesized.…”
Section: Peroxidase Mimetic Nanozymes In Oxygen-dependent Cancer Photodynamic Therapymentioning
confidence: 99%